Impact of Malathion Toxicity on Acetyl Choline Esterase Activity in ‘Carassius auratus’ (Linnaeus, 1758) and Botia striata (Narayan Rao, 1920) - Raj, Manju V.; K., Sherin; K., Sheeba; P. S., Sherly (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Fishes are considered as the bio-indicator species to monitor water pollution. Malathion, an organophosphate pesticide widely utilized in agriculture across Kerala and other Indian states, is a potent insecticidal agent. This study aims to assess the impact of malathion on acetyl choline esterase (AchE) activity in various tissues of Carassius auratus and Botia striata. Separately, both fish species were subjected to a sub-lethal concentration of 3.4 ppm malathion for 48, 72, and 96 hours, followed by a recovery period of 15 days. The quantification of AchE activity was done using Ellman’s method. In the control group, highest activity was observed in brain and muscle, with moderate activity in liver, and kidney. In C. auratus, following 72 hours of exposure, AchE activity significantly declined from 7.2 to 1.8 in the brain and in B.striata, the value declined from 5.7 to 1.4. In C. auratus, there was a gradual recovery with activity reaching 5.26, and in B.striata recovery activity reached 4.46 by the end of 15-days. In case of kidney in C. auratus, the AchE activity was found to show variation with fluctuating values while in B.striata an abnormal AchE activity was found in recovery period. The findings highlight the severe neurotoxic effects of malathion on aquatic organisms and its potential risks to environmental health and biodiversity. Moreover, the persistent use of another organophosphate pesticide, endosulfan in Kasaragod district, Kerala, has led to detrimental effects on human populations, including children. This poses the concern of the prolonged usage of malathion on human population. Reports indicate chromosomal abnormalities and genetic mutations, with the possibility of these defects being transmitted across generations. This study underscores the urgent need for regulatory measures to mitigate the environmental and public health risks posed by malathion.